TERMINOLOGI “RANGKAIAN PRODUKSI BARANG/JASA TERTENTU” YANG MENGAKIBATKAN PERSAINGAN USAHA TIDAK SEHAT (STUDI PUTUSAN- PUTUSAN KPPU TERKAIT PASAL 14 UUNO 5/1999): The Terminology of “Production Series Of Certain Product/Services” Result In Unfair Business Competition (Study Of KPPU's Decisions Related To Article 14 Of Law No 5/1999 - Anriyani, Dian; Anggraini, Ana Maria Tri (AMICUS CURIAE, 2024)
The series of production of goods/services which results in business competition and/or harms the community is called Vertical Integration as regulated in Article 14 of Law No. 5 of 1999 and Implementation Guideline 14 concerning Vertical Integration. Whereas a series of production of certain goods/services that aim to control production is a prohibited agreement. The main problem in this journal is how is the definition of a series of production of certain goods/services according to Law No. 5 of 1999 and the Implementing Regulations and how KPPU applies the definition of a series of production of certain goods/services Case Decision No. 01/KPPU- L/2003, Decision No. 13 /KPPU-I/2014 and Decision No. 13/KPPU-I/2019. The research method used is normative law by using secondary data supported by interviews, the method of collecting data using literature studies, qualitative analysis, and concluding by deductive methods. The production chain research concludes that several stages must be carried out starting from the collection of raw materials to processing them into semi- finished products and finished products, these stages cover from upstream to downstream, which means that the production chain is a business activity that is carried out as a single unit starting from process to the final stage that can be consumed by the community.